2015
DOI: 10.1111/cch.12267
|View full text |Cite
|
Sign up to set email alerts
|

Associations between family characteristics and parental empowerment in the family, family service situations and the family service system

Abstract: Summary Background Parental empowerment signifies parents' sense of confidence in managing their children, interacting with services that their children use and improving child care services. High empowerment is associated with parents' resilience to demands and their confidence to make decisions and take actions that positively affect their families. Most families with children access various healthcare and education services. Professionals working in these services are therefore ideally placed to reinforce p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
2
25
0
4
Order By: Relevance
“…Promoting parental self‐confidence and providing appropriate emotional and concrete support for everyday functioning may reinforce parental empowerment, thereby enhancing families' well‐being and coping, as well as improving their access to required services (Vuorenmaa et al . ). In our study we found evidence of a need for this.…”
Section: Discussionmentioning
confidence: 97%
“…Promoting parental self‐confidence and providing appropriate emotional and concrete support for everyday functioning may reinforce parental empowerment, thereby enhancing families' well‐being and coping, as well as improving their access to required services (Vuorenmaa et al . ). In our study we found evidence of a need for this.…”
Section: Discussionmentioning
confidence: 97%
“…Functional performance of children with cerebral palsy is directly influenced by the therapeutic guidelines offered to caregivers 2 . Health education thus becomes a vital component of early intervention; based on a familycentered approach or practice, providing mechanisms and strategies for family empowerment, intensity and continuity of care, promoting better family adaptation to children with disabilities, lower levels of stress, anxiety and family frustration 3 ; In addition to providing children with many and better opportunities for active practice within their daily routines 4 . It is understood today that the health team must be able to understand the experiences and guide the parents and/or caregivers of children with disabilities; to listen to them and to recognize them as part of a joint strategy of coping and comprehensive rehabilitation of these children 5 .…”
mentioning
confidence: 99%
“…Promover autoconfiança e proporcionar apoio psicológico adequado para um melhor desempenho do dia a dia familiar pode intensificar o empoderamento dos pais, propiciando bem-estar, o enfrentamento saudável da condição de vida, melhora no acesso e no apoio aos serviços necessários e facilidade na prestação de melhores serviços para as famílias (38) . No que se refere às abordagens centradas na família, o empoderamento parental é essencial, principalmente oferecendo condições necessárias para que os pais sejam capazes de se autoavaliar no que diz respeito à gestão de seus filhos, estando diretamente relacionado aos recursos internos e à capacidade de apropriação da vida (39) .…”
Section: () Será Que Eles Não Sentem Dor De Cabeça Por Causa Da MIunclassified
“…A escassez de medidas específicas, que identifiquem adequadamente as necessidades dos pais de crianças nessa condição, é notória (48) . Dessa forma, os profissionais de saúde que atendem famílias podem e devem reforçar os recursos parentais, apoiando o envolvimento deles na tomada de decisões relativas à sua criança e vida familiar, contribuindo assim significativamente para a consolidação do bem-estar de todos os envolvidos (38) . Com base nas descobertas do atual estudo, corrobora-se que os profissionais de saúde podem e devem subsidiar a capacitação parental de forma permanente e continuada, reforçando o empoderamento dos pais e familiares de crianças com microcefalia por ZIKV com de uma abordagem contínua através de visitas domiciliares e do envolvimento dos pais em cada fase do tratamento dos filhos (41) .…”
Section: ) (Participante 04)unclassified